ADAPTATION AND PRODUCTIVITY OF SPRING BREAD AND DURUM WHEAT DEPENDING ON CONDITIONS IN KAZAKHSTAN AND RUSSIA (Experimental biology, 2025)
The study is devoted to a comparative analysis of adaptation and productivity of spring bread (Triticum aestivum L.) and durum (Triticum durum Desf.) wheat in the agroecological conditions of Kazakhstan and Russia. The aim of the work was to determine the differences between these crops in response to growing conditions in the main cultivation regions in order to increase the efficiency of breeding and production. The scientific and practical significance of the work lies in identifying the specific features of adaptation of each wheat species, which will allow a more informed approach to their placement in crop rotations and the development of varietal technologies. The research methodology is based on the analysis of the results of long-term (2005-2024) field experiments of the Kazakhstan-Siberian Network for Spring Wheat Improvement (KASIB) in four scientific institutions: Karabalyk Agricultural Experimental Station (AES), Aktobe AES (Kazakhstan), Altai Scientific Center of Agrobiotechnologies and Omsk Agricultural Research Center (Russia). The results showed that spring bread wheat in Kazakhstan conditions demonstrates higher yield than durum (by 7-21%), even though durum wheat forms taller plants and has a larger 1000 grain weight. In Western Siberia (Altai Territory), durum wheat outperformed bread wheat in yield by 8.6%. A strong positive correlation was established between yield and plant height, 1000 grain weight in both wheat species. Higher sensitivity of spring bread wheat to elevated air temperatures in June and for the May-July period was revealed. The value of the study lies in a comprehensive comparative analysis of two species grown under identical conditions, which allowed identifying their specific response to environmental factors. The practical significance of the work consists in the possibility of a more informed choice of wheat species for specific agroecological conditions and the development of breeding strategies specific to each species.
Keywords: spring bread wheat, spring durum wheat, adaptation, productivity, correlation, weather conditions.